2015
DOI: 10.1080/13548506.2015.1073337
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of successful smoking cessation by psychological factors using the Bayesian network approach

Abstract: The association between psychological factors and smoking cessation is complicated and inconsistent in published researches, and the joint effect of psychological factors on smoking cessation is unclear. This study explored how psychological factors jointly affect the success of smoking cessation using a Bayesian network approach. A community-based case control study was designed with 642 adult male successful smoking quitters as the cases, and 700 adult male failed smoking quitters as the controls. General se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In the field of occupational health and safety, the one that concerns us, there are several examples of the application of Bayesian networks. As examples, Zhou et al [ 52 ] proposed a model to analyze the influence of climate safety factors and personal experience on human behavior; Yang et al [ 53 ] evaluated the relationship between psychological factors and successful smoking cessation; Akhtar and Utne [ 54 ] calculated the risk of human fatigue in maritime accidents; García-Herrero et al [ 55 ] analyzed the influence of working conditions on occupational accidents; Moret-Tatay et al [ 56 ] examined the relationships, in terms of probabilities, between gender, coping, and mental health.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of occupational health and safety, the one that concerns us, there are several examples of the application of Bayesian networks. As examples, Zhou et al [ 52 ] proposed a model to analyze the influence of climate safety factors and personal experience on human behavior; Yang et al [ 53 ] evaluated the relationship between psychological factors and successful smoking cessation; Akhtar and Utne [ 54 ] calculated the risk of human fatigue in maritime accidents; García-Herrero et al [ 55 ] analyzed the influence of working conditions on occupational accidents; Moret-Tatay et al [ 56 ] examined the relationships, in terms of probabilities, between gender, coping, and mental health.…”
Section: Introductionmentioning
confidence: 99%
“…For couples planning to deliver babies, pharmacological interventions are not applicable nor acceptable; as a result, non-pharmacological interventions such as effective health education can play a more important role, especially for persistent maternal smokers. Previous studies indicated that giving health warning messages that fit smokers’ personal circumstances and psychological factors can effectively affect smokers’ subjective beliefs about the harms of smoking, which in turn would affect their intentions and decisions 35 36. Relative counselling should be adopted to help smokers to deal with adverse reactions during smoking cessation, such as nicotine withdrawal, which may obstruct their persistence to quit,37 and psychosocial interventions should be provided to help them to cope with mood problems and to enhance external self-efficacy to resist temptation and social influences 38…”
Section: Discussionmentioning
confidence: 99%
“…For paternal risk factors, paternal smoking, paternal drinking, and paternal exposed to new house decoration were all associated with stillbirth after adjustment of paternal age. In rural China, male smoking and drinking are still severe public health problems that need to be addressed 43,44 . New decorated house may be associated with higher dosage level of formaldehyde or organic solvent, which were reported to be risk factors of stillbirth 45 .…”
Section: Discussionmentioning
confidence: 99%